THE REASONS FOR LAYOFFS BY COMPANIES ARE BASED ON THE LAYOFF PROVISIONS IN LAW NO. 11 OF 2020 CONCERNING JOB CREATION AGAINST INDUSTRIAL RELATIONS COURT DECISIONS DUE TO GROSS ERRORS (PN DECISION STUDY NUMBER 1 / PDT. SUS-PHI/2021/PN PGP) - Muchamad Fachmi Fachrezi; Palmawati Tahir; Rani Sri Agustina (Universitas Muhammadiyah Tangerang, 2023)
District Court Decision Number 1/Pdt.Sus-PHI/2021/PN Pgp, where the position of workers tends to have no power, when dealing with employers who have the power Unilateral termination of employment carried out by PT Sinarmas Multifinance to the workers, namely Welson Fransisca, Heri Ferdian and Rudi Karmidi as employees of PT Sinarmas Multifinance, they are accused of serious mistakes and layoffs by means of the first SP and the second SP without any court decision previously. With so many cases like this, workers lose the opportunity and justice legally, which will harm the workers. This study aims to find out the reasons for layoffs by PT Sinarmas Multifinance whether they can be justified in accordance with the layoff provisions based on Law No. 11 of 2020 concerning Job Creation. Based on Law No. 11 of 2020 concerning Job Creation, it is explained that the reason for the layoffs by PT Sinarmas Multifinance cannot be justified in accordance with the layoff provisions in Article 52 paragraph 1 of PP No. 35 of 2021, between the 1st and 2nd Warning Letters given by PT. Sinarmas Multifinance. Sinarmas Multifinance exceeds the period of 6 months since its issuance. Then it should be inappropriate and categorized as an act of layoff without error.Keywords: Workers/Laborers, Gross Mistakes, Labor Law